Biomass Nutrient Profiles of Marine Microalgae Dunaliella salina - Moh. Muhaemin Moh. Muhaemin; Richardus F. Kaswadji (Faculty of Mathtmatics and Natural Sciences, 2010)
The unconventional micro algal sources for the production of feed, food, food additive, pharmaceutical, and fine chemical is growing in important. Researches in the field are expanding worldwide. Nutritional composition of marine micro algae Dunaliella salina data included proximate composition, nitrate, RNA, and pigments were analyzed under various conditions in semi cultured medium. On average, nutritional composition of biomass was highly influenced by external irradiance and residence time in bioreactor. The biomass collected for short residence times was richer in protein.